2010
DOI: 10.1186/1471-2458-10-240
|View full text |Cite
|
Sign up to set email alerts
|

The association between green space and cause-specific mortality in urban New Zealand: an ecological analysis of green space utility

Abstract: BackgroundThere is mounting international evidence that exposure to green environments is associated with health benefits, including lower mortality rates. Consequently, it has been suggested that the uneven distribution of such environments may contribute to health inequalities. Possible causative mechanisms behind the green space and health relationship include the provision of physical activity opportunities, facilitation of social contact and the restorative effects of nature. In the New Zealand context we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 32 publications
8
155
4
3
Order By: Relevance
“…Our results are consistent with studies from the UK [4,15], which found negative associations between green space and mortality for all-cause, cardiovascular, and respiratory mortality, but not lung cancer mortality, but not with a study from New Zealand [16], which found no association between green space and mortality from either cardiovascular diseases or lung cancer.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results are consistent with studies from the UK [4,15], which found negative associations between green space and mortality for all-cause, cardiovascular, and respiratory mortality, but not lung cancer mortality, but not with a study from New Zealand [16], which found no association between green space and mortality from either cardiovascular diseases or lung cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Several mechanisms by which green space might reduce mortality from certain diseases have been proposed, including promotion of physical activity, stress reduction, and increasing social contact [15,16]. Prior studies have provided evidence that more physical activity is associated with lower cardiovascular and respiratory mortality [15] and that stress may exacerbate, and social support ameliorate, cardiovascular diseases [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been very few epidemiological studies in the UK examining the relation between urban-rural features and mental health and no total population studies in Scotland. The geographical landscape (Scottish Government, 2011), the pattern of deprivation (Fairburn et al, 2005), and significant mental health issues in Scotland (Scottish Association for Mental Health, 2011) as well as the fact that the results obtained from one country cannot necessarily be generalised to other countries (Richardson et al, 2010) provides a rationale for conducting such research in Scotland.…”
Section: Aims Of Studymentioning
confidence: 99%
“…Specific land use types are also found correlated to respiratory health. For instance, residences near industrial areas are significantly associated with various disease incidences including lung cancer (37)(38)(39); green spaces have a positive impact on health, including decreasing respiratory disease mortality (40)(41)(42), while the impact may not always significant in certain areas (43). Meanwhile, since high traffic volume increases incidence rate of pulmonary adenoma (44,45), living within 100 m from highways has a negative impact on respiratory health for both children (46,47) and adults (48).…”
Section: Introductionmentioning
confidence: 99%